Assigning meanings to school mathematical knowledge by students of early education - Kalinowska, Alina (Studia Pedagogiczne, 2015)
For many years, learning the competences to teach mathematics in early education at university has been associated with the ability to reproductively apply methodological guidelines. Currently, however, the need to not only understand the mathematical meanings given by teachers, but also students of the specialty, are seen to be important. This article attempts to engage in an interpretive line of thinking with regard to mathematics education, coming from the perspective of students learning to be early education teachers. Their understanding of the contexts for learning mathematical concepts, as well as their sensitivity to the processes of constructing mathematical knowledge by very young pupils, being a way of predicting what educational activities will be undertaken in the classroom in the future. This text is the result of qualitative analyses of written essays of early education students, where respondents had to make conceptualizations of their beliefs by justifying the selection of particular declarative statements. Students’ mathematical meanings were also uncovered in their strategies for solving mathematical problems for very young pupils. Moreover, the results of this analyses provides a context for reading the students’ understanding of mathematics learning processes.
Keywords: constructivism; mathematical meanings; teaching math in early education